Scanning tunneling microscope operating as a spin diode - Penteado, P. H.; Souza, F. M.; Seridonio, A. C. [UNESP]; Vernek, E.; Egues, J. C. (American Physical Society (APS), 2011)
We theoretically investigate spin-polarized transport in a system composed of a ferromagnetic scanning-tunneling-microscope (STM) tip coupled to an adsorbed atom (adatom) on a host surface. Electrons can tunnel directly from the tip to the surface or via the adatom. Since the tip is ferromagnetic and the host surface (metal or semiconductor) is nonmagnetic we obtain a spin-diode effect when the adatom is in the regime of single occupancy. This effect leads to an unpolarized current for direct bias (V>0) and polarized current for reverse (V<0) bias voltages, if the tip is nearby the adatom. Within the nonequilibrium Keldysh technique we analyze the interplay between the lateral displacement of the tip and the intra adatom Coulomb interaction on the spin-diode effect. As the tip moves away from the adatom the spin-diode effect vanishes and the currents become polarized for both V>0 and V<0. We also find an imbalance between the up and down spin populations in the adatom, which can be tuned by the tip position and the bias. Finally, due to the presence of the adsorbate on the surface, we observe spin-resolved Friedel oscillations in the current, which reflects the oscillations in the calculated local density of states (LDOS) of the subsystem surface + adatom. © 2011 American Physical Society.